Biguanide MC001, a Dual Inhibitor of OXPHOS and Glycolysis, Shows Enhanced Antitumor Activity Without Increasing Lactate Production. (18th January 2022) - Fu, Jiamiao; Liu, Siyu; Hu, Minqiang; Liao, Ximing; Wang, Xiaoquan; Xu, Zhengshuang; Li, Qinkai; Quan, Junmin
Abstract: Metformin and other biguanides represent a new class of inhibitors of mitochondrial complex I that show promising antitumor effects. However, stronger inhibition of mitochondrial complex I is generally associated with upregulation of glycolysis and higher risk of lactic acidosis. Herein we report a novel biguanide derivative, N ‐cystaminylbiguanide (MC001), which was found to inhibit mitochondrial complex I with higher potency while inducing lactate production to a similar degree as metformin.Furthermore, MC001 was found to efficiently inhibit a panel of colorectal cancer (CRC) cells in vitro and to suppress tumor growth in a HCT116 xenograft nude mouse model, while not enhancing lactate production relative to metformin, exhibiting a superior safety profile to other potent biguanides such as phenformin. Mechanistically, MC001 efficiently inhibits mitochondrial complex I, activates AMPK, and represses mTOR, leading to cell‐cycle arrest and apoptosis. Notably, MC001 inhibits both oxidative phosphorylation (OXPHOS) and glycolysis. We therefore propose that MC001 warrants further investigation in cancer treatment. Abstract : Biguanide inhibits both OXPHOS and glycolysis : We report a novel biguanide derivative, N ‐cystaminylbiguanide (MC001), that efficiently inhibits mitochondrial complex I, while not enhancing lactate production relative to metformin. MC001 inhibits both oxidative phosphorylation and glycolysis, and exhibits much more potent antitumor activity in vitro and in vivo than metformin.